PERAN GURU PENDIDIKAN AGAMA ISLAM PADA PEMBELAJARAN AUGMENTED REALITY - Iis Ibrahim; Imas Baguna; Kholid Mootalu; Roymanto Ilolu (LPPM Universitas Muhammadiyah Gorontalo, 2026)
The Role of Islamic Religious Education Teachers in Implementing Augmented Reality Learning Media. Low student learning motivation caused by the predominance of conventional teaching methods encourages the need for innovative technology-based learning in Islamic Religious Education. This study aimed to analyze the role of Islamic Religious Education teachers in implementing Augmented Reality (AR) learning media, examine its impact on students' learning motivation, and identify the challenges encountered during its implementation at Madrasah Aliyah Al-Falah Limboto Barat. This study employed a qualitative field research approach involving the principal, Islamic Religious Education teachers, and students as research participants. Data were collected through observation, interviews, documentation, and a learning motivation questionnaire, and were analyzed using data reduction, data display, and conclusion drawing. The findings revealed that teachers played strategic roles as learning planners, facilitators, motivators, mentors, and evaluators in integrating AR into classroom instruction. The implementation of AR learning media increased students' attention, participation, interest, and enthusiasm during the learning process. The questionnaire results showed that 85% of students were categorized as having high learning motivation after the implementation of AR learning media. The study concludes that the effective implementation of AR-based learning depends not only on technological innovation but also on teachers' pedagogical competence and their ability to manage technology-integrated learning effectively